The effect of mixed herbs on blood glucose and lipid profile in case controlled type 2 diabetes mellitus (T2DM) - Mahmood, Tahir; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nor Azwani; Azam, Siti Amirah; Nurul , Aimi (2014)

(untitled)
The prevalence of type 2 diabetes mellitus (T2DM) continues to rise in an exponential rate so as the oral hypoglycemic agents (OHA) and their worsening effects. The aim of this study was to evaluate the effects of mixed herbs, as ad-on therapy on blood sugar and lipid profile of the patients with T2DM. The dietary manipulations in the form of mixed herbs have been shown to be effective in controlling the hyperglycemia both in animal and human. A total 20 patients consented and were equally divided into control and the test groups. The patients were fed either with the placebo or mixed herbs preparation 4 g daily for 30 days. Blood samples were collected before and at the end of the feeding period and analyzed for the parameters namely Fasting Blood Sugar (FBS), 2 hours post prandial (2HPP) Glycosylated Hb (HbA1c) and Lipid Profile. The collected data was analyzed using SPSS Statistical Software version 12. The protocol of the study was approved by the International Islamic Medical University Malaysia Research Ethical Committee and the Clinical Research Committee (CRC) Ministry of Health Malaysia. Most of the patients tolerated the preparation very well and observed an improvement in their general well-being. The results show a decreasing trends in FBS and HbA1c in the test group but the difference remained statistically insignificant (P>0.05). The formulated preparation highlights the significance of these mixed herbs for diabetics as ad-on nutritional supplement in the management of T2DM patients, which might be helpful in minimizing the long term complications as well as the huge economic cost linked to this most severe pandemic of the 21st century (T2DM).